Tillage, crop residue management and nitrogen application impacts on crop productivity under maize-wheat cropping system - R.S. Ghuman; Harmeet Singh (Annals of Agricultural Research, 2023)
Tillage, crop residue and fertilizer-N application can impact soil properties and crop productivity. Therefore, we assessed the effect of tillage (deep tillage [DT] vs. shallow tillage [ST]), residue management viz. conventional tillage without residue (CT-R), conventional tillage with residue (CT+R), minimum tillage without residue (MT-R) and minimum tillage with residue (MT+R) and Fertilizer-N at 75, 100 and 125% N (viz. N75, N100 and N125) on maize-wheat system in two locations of Punjab during 2016-18. Results of the study showed that, the tillage and residue combination treatments under this study (CT-R, CT+R, MT-R and MT+R) did not significantly influence the grain yield or other growth parameters of maize and wheat. At Ladhowal, themaize grain yield was significantly enhanced by 8-12% under DT during 2017-2018 crop seasons. Similarly, DTdid not significantly affect the wheat yield but, increased the maize yield by 8 to 12 % at one of the two sites which had heavy soil. However, fertilizer application at N125 treatment recorded significantly higher growth attributes and yield both in maize and wheat as compared to N75, but remained statistically at par with N100